The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/s1677-5538.ibju.2015.0002
|View full text |Cite
|
Sign up to set email alerts
|

Severity of erectile dysfunction is highly correlated with the syntax score in patients undergoing coronariography

Abstract: Objective To investigate the association between the severity of erectile dysfunction (ED) and coronary artery disease (CAD) in men undergoing coronary angiography for angina or acute myocardial infarct (AMI).Material and Methods We studied 132 males who underwent coronary angiography for first time between January and November 2010. ED severity was assessed by the international index of erectile function (IIEF-5) and CAD severity was assessed by the Syntax score. Patients with CAD (cases) and without CAD (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Similar data were recently reported in a study of 100 patients of both genders undergoing coronary angiography for diagnostic purposes, showing that 37% of those patients had no atherosclerotic lesions 12 . Our hypothesis is also supported by other authors, whom have emphasized the absence of non-invasive methods, clinical symptoms or laboratory tests that are capable of detecting individuals who will develop CAD 1 .…”
Section: Discusssionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar data were recently reported in a study of 100 patients of both genders undergoing coronary angiography for diagnostic purposes, showing that 37% of those patients had no atherosclerotic lesions 12 . Our hypothesis is also supported by other authors, whom have emphasized the absence of non-invasive methods, clinical symptoms or laboratory tests that are capable of detecting individuals who will develop CAD 1 .…”
Section: Discusssionsupporting
confidence: 81%
“…Cardiovascular disease is the leading cause of death worldwide. Obtaining knowledge about its physiopathology seems to be the best approach to reducing morbidity, mortality, and health care costs, since there are no non-invasive methods, laboratory tests or clinical symptoms that are capable of detecting which individuals will develop coronary artery disease (CAD) 1 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 9 The severity of erectile dysfunction, which is evaluated by the 5-item version of the International Index of Erectile Function, was also reported to correlate with CVD and may lead to a difference in specific CVD outcomes. 10 12 …”
Section: Introductionmentioning
confidence: 99%
“…IIEF-5 could initially be applied to the assessment of ED. 25 Andrade et al 26 reported that the IIEF-5 score of the patients without CAD was significantly higher than the score of the patients with CAD. Moreover, urologists' evaluation of CVDs in patients with ED was also not updated.…”
Section: Discussionmentioning
confidence: 98%